The night manager : [the complete series] - Bier, Susanne, 1960-; Colman, Olivia; Hiddleston, Tom; Hollander, Tom, 1967-; Laurie, Hugh, 1959-; Le Carré, John, 1931-2020 (2016)
Jonathan Pine is working as the night manager of a Cairo hotel. He gets involved with a local woman who is the girlfriend of a local gangster. Through her relationship with the gangster she has acquired information linking illegal international arms sales with an English billionaire.